Abnormal ac4C modification in metabolic dysfunction associated steatotic liver cells - Xiqian Zhang; Yaxian Zheng; Jing Yang; Yan Yang; Qin He; Min Xu; Fangyi Long; Yujie Yang (Scientific Reports)
Abstract The pathogenesis of metabolic dysfunction-associated steatotic liver disease (MASLD) remains unclear due to the complexity of its etiology. The emerging field of the epitranscriptome has shown significant promise in advancing the understanding of disease pathogenesis and developing new therapeutic approaches. Recent research has demonstrated that N4-acetylcytosine (ac4C), an RNA modification within the epitranscriptome, is implicated in progression of various diseases. However, the role of ac4C modification in MASLD remains unexplored. Herein, we performed acRIP-ac4c-seq and RNA-seq analysis in free fatty acids-induced MASLD model cells, identifying 2128 differentially acetylated ac4C sites, with 1031 hyperacetylated and 1097 hypoacetylated peaks in MASLD model cells. Functional enrichments analysis showed that ac4C differentially modified genes were significantly involved in processes related to MASLD, such as nuclear transport and MAP kinase (MAPK) signaling pathway. We also identified 341 differentially expressed genes (DEGs), including 61 lncRNAs and 280 mRNAs, between control and MASLD model cells. Bioinformatics analysis showed that DEGs were significantly enriched in long-chain fatty acid biosynthetic process. Notably, 118 genes exhibited significant changes in both ac4C modification and expression levels in MASLD model cells. Among these proteins, JUN, caveolin-1 (CAV1), fatty acid synthase (FASN), and heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) were identified as core proteins through protein–protein interaction (PPI) network analysis using cytoscape software. Collectively, our findings establish a positive correlation between ac4C modification and the pathogenesis of MASLD and suggest that ac4C modification may serve as a therapeutic target for MASLD.